Pentingnya Perencanaan dalam Melakukan Aktifitas untuk Mendukung Produktifitas Individu Dewasa dengan ADHD - Santoso, Tri Budi (Politeknik Kesehatan Kemenkes Surakarta, 2024)
Abstract Background: ADHD conditions cause adult individuals to experience various difficulties in carrying out daily activities, both when working and carrying out activities on campus. Objectives: This study explores the benefits of activity planning to support the productivity of adult individuals diagnosed with ADHD. Methods: This qualitative research using the phenomenological method involved eight adult individual participants with ADHD. We collected data through interviews and observations. We used thematic analysis to analyze the collected data. Results: Two themes emerged from the thematic data analysis. The first theme,